Helicobacter pylori resistance to antibiotics in Europe in 2018 and its relationship to antibiotic consumption in the community. Issue 10 (9th April 2021) - Megraud, Francis; Bruyndonckx, Robin; Coenen, Samuel; Wittkop, Linda; Huang, Te-Din; Hoebeke, Martin; Bénéjat, Lucie; Lehours, Philippe; Goossens, Herman; Glupczynski, Youri
Abstract : Objective: Our aim was to prospectively assess the antibiotic resistance rates in Helicobacter pylori strains in Europe in 2018 and to study the link between antibiotic consumption in the community and H. pylori resistance levels in the different countries. Design: The proportion of primary antibiotic resistance cases of H. pylori and their corresponding risk factors were investigated in 24 centres from 18 European countries according to a standardised protocol. Data on antibiotic consumption in the community were collected for the period 2008–2017. The link between antibiotic consumption and resistance data was assessed using generalised linear mixed models. The model with the best fit was selected by means of the Akaike Information Criterion. Results: H. pylori resistance rates for the 1211 adult patients included were 21.4% for clarithromycin, 15.8% for levofloxacin and 38.9% for metronidazole and were significantly higher in Central/Western and Southern than in the Northern European countries. The best model fit was obtained for the Poisson distribution using 2013 consumption data. A signiﬁcant association was found between H. pylori clarithromycin resistance and consumption in the community of macrolides (p=0.0003) and intermediate-acting macrolides (p=0.005), and between levoﬂoxacin resistance and consumption of quinolones (p=0.0002) and second-generation quinolones (p=0.0003). Conclusion: This study confirms the positive correlation between macrolide and quinolone consumption in the community and corresponding H. pylori resistance in European countries. Hence, H. pylori treatment with clarithromycin and levofloxacin should not be started without susceptibility testing in most European countries.